The law is a factish - Wink, James (Department of Private Law, 2017)
Drawing upon the work of Bruno Latour, this dissertation defends the thesis that the law is a factish: an indivisible blend of social and natural reality. The dissertation develops, in Latour's terms, a "non-modern" framework from which it draws, in turn, the philosophical foundations for a theory of factish law. This framework is presented as a paradoxical model of understanding, which situates the law within a broader understanding of reality. The model allows for several distinctions of modern analytical philosophy to be breached, without succumbing to a post-modern paralysis of thought. Applied within jurisprudence, it allows for an account of the law as factish that avoids the clash between positivism and natural law, preferring instead to draw upon insights from each tradition. This factish understanding of the law founds several related observations that together constitute the formative steps towards a theory of factish law. Instead of viewing the law as completely unique, the aspiration towards inviolability is identified as a central attribute of law, shared by actors as diverse as the laws of physics and the laws of the State, whilst the absence of this aspiration from customary law distinguishes it from the law without needing to create an implicit hierarchy of normative systems. Having explicated factish law, the dissertation moves to a proposed model of factish legality, drawing upon the model of paradoxical understanding, in order to explain the process by which the law is created. Alternate understandings of the rule of law and the separation of powers are posited in accordance with this model, as opposed to the dominant views expressed by South African jurists. Having established some of the theoretical commitments of factish law, the dissertation then focuses on the question of justifying the law in South Africa. In the course of the argument, the relationship between law and violence, the distortionary effects of South Africa‟s celebrated Bill of Rights and the contemporary demand for "African" South African law are considered and critiqued.